Childhood-onset Caroli’s disease as a cause of recurrent fever: A case report - Sun, Jing; Wang, Sheng; Chen, Biquan (Frontiers in Pediatrics, 2022)
Caroli's disease is a rare congenital bile duct malformation characterized by intrahepatic bile duct dilatation. This kind of situation is seldom encountered in clinical work. We report such a case who presented to our emergency department with recurrent fever as initial symptom. According to the clinical manifestation and imaging examination, a 13‑year‑old boy was diagnosed with suppurative cholangitis and sepsis caused by Caroli's disease. The symptoms were got relieved after antibiotic therapy upgraded from cephalosporins to carbapenems. After 5 months of follow-up, he did not have fever, abdominal pain or any other discomfort. We believe the present report is of medical significance since it serves as a reminder that Caroli’s disease may have atypical presentations and be masked by non-specific clinical findings. The report hopes to enlighten our pediatric colleagues by providing more knowledge on such rare congenital disease.